Design, síntese e caracterização de ligas multicomponentes contendo Mg para armazenagem de hidrogênio - Ferraz, Mariana de Brito (2022)
The use of hydrogen as an alternative fuel has been investigated due to its great potential to be used as an energy vector. One of the challenges for its wide application is to store it safely and efficiently. Therefore, metallic hydrides have been studied as a promising alternative for hydrogen storage in solid state. Moreover, multicomponent (MC) alloys are currently gaining attention because they can increase the possibility of obtaining materials for this application, due to their large compositional field. Recently, it was reported in the literature that some alloys with body centered cubic (BCC) structure present high storage capacity. There are many works dedicated to the study of MCs alloys composed only by transition metals, which ends up limiting the gravimetric capacity, due to the density. Therefore, the use of the element Mg in the composition of these alloys is proposed, since it has low density and good affinity with hydrogen. The present work made use of the parameters ∅, Ω, (%) and VEC, as a method of composition selection, which resulted in the alloy Mg35Al15Ti25V10Zn15. This alloy was synthesized by mechanical alloy (MA) and reactive milling (RM), structurally characterized and its hydrogen storage properties were analyzed. The alloy produced by MA was composed of a BCC phase, with an amount of unmixed Mg, absorbing about 2.5 %p. of H2 at 375°C and 4 MPa. The alloy produced by RM was composed of a mixture of a face centered cubic (FCC) hydride and MgH2, having a desorption capacity of 2.75 %p. H2. Furthermore, the desorption behavior was analyzed, and it was observed that MgH2 is the first to desorb and the desorption sequence is complete after the decomposition of the FCC and body centered tetragonal (BCT) phases, leading to the formation of the BCC phase.